2005
DOI: 10.1081/ss-200042239
|View full text |Cite
|
Sign up to set email alerts
|

Cesium Removal from Savannah River Site Radioactive Waste using the Caustic-Side Solvent Extraction (CSSX) Process

Abstract: Researchers at the Savannah River Technology Center (SRTC) successfully demonstrated the Caustic-Side Solvent Extraction (CSSX) process flow sheet using a 33-stage, 2-cm centrifugal contactor apparatus in two 24-hour tests using actual high level waste. The CSSX process for removal of cesium from alkaline solutions is the reference process for decontamination of high level waste (HLW) at the Savannah River Site (SRS). The solvent consists of a calix [4]arene-crown-6 extractant (BOBCalix), an alkylphenoxy alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…The calculations employed arbitrary, but reasonable, stage efficiencies of 80% to estimate the "actual" number of stages shown; these may be compared with the slightly greater "theoretical" stages assuming that stage efficiencies are 100% (i.e., running at equilibrium). Four scrub stages were arbitrarily assumed, though two are used at the SRS and presumed sufficient [8][9][10]. No wash stages were included, as they would not be expected to influence the results; however, two wash stages with 10 mM NaOH, as used at the SRS, are likely necessary for long-term process stability.…”
Section: Flowsheet Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The calculations employed arbitrary, but reasonable, stage efficiencies of 80% to estimate the "actual" number of stages shown; these may be compared with the slightly greater "theoretical" stages assuming that stage efficiencies are 100% (i.e., running at equilibrium). Four scrub stages were arbitrarily assumed, though two are used at the SRS and presumed sufficient [8][9][10]. No wash stages were included, as they would not be expected to influence the results; however, two wash stages with 10 mM NaOH, as used at the SRS, are likely necessary for long-term process stability.…”
Section: Flowsheet Designmentioning
confidence: 99%
“…The process as currently practiced has been optimized [2][3][4][5][6] and demonstrated [7][8][9] for removal of cesium from salt waste at the Savannah River Site (SRS). To meet the needs of the SRS Salt Waste Processing Facility (SWPF) [10], the CSSX process has been designed and demonstrated to remove cesium with a decontamination factor (DF) in excess of 40,000, concentrating it by a factor (CF) of 15 in a stream of 1 mM HNO 3 suitable for vitrification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of metal ions of biological [1,2], medicinal [3,4], radioactive [5,6] and environmental significance [7] is an area of intense research activity [8,9]. Owing to the presence of distinct hydrophobic and hydrophilic regions and adjustable cavity dimensions in their molecular architecture, calixarenes have attracted considerable attention for the design of useful receptors [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Since both uranium and plutonium can be separated through the use of a 30% tri-n-butyl phosphate/kerosene mixture, the HNO 3 concentration in the HLW produced is usually ca. 3.0 M. A number of liquid-liquid solvent-extraction partitioning techniques, such as transuranic extraction (TRUEX) (Schulz and Horwitz 1988), universal solvent extraction (UNEX) Romanovskiy et al 2001;Herbst et al 2002), caustic-side solvent extraction (CSSX) (Walker et al 2003), strontium extraction (SREX) (Horwitz et al 1991;Wood and Law 1997), caesium separation by crown-calix extraction (CCCEX) (Simon et al 2000(Simon et al , 2004 and fission product extraction (FPEX) (Riddle et al 2005;Mincher et al 2007), have been reported as providing an effective separation of the long-lived minor actinides, Sr(II) and Cs(I) by utilizing a variety of chelating extractants in a hydrocarbon diluent. Some macrocyclic crown-calix[4]arene ether-containing compounds such as calix [4]arene-bis(t-octylbenzo-crown-6) (BOBcalixC6) and 4,4′,(5′)-di(t-butylcyclohexano)-18-crown-6 (DtBuCH18C6) dissolved in ISOPAR ® L diluent exhibit excellent extraction capabilities and selectivities for Sr(II) (Law et al 1997).…”
Section: Introductionmentioning
confidence: 99%